Photo-thermionic effect in vertical graphene heterostructures - M. Massicotte (Nature Portfolio, 2016)
The detection of low-energy photons may be enabled by devices that make use of the excess thermal energy from photoexcited carriers as a result of light absorption. Here the authors demonstrate a vertical graphene-WSe2-graphene heterostructure that takes advantage of the photo-thermionic effect.